Lack of interactions between breast cancer resistance protein (bcrp/abcg2) and selected antiepileptic agents - Červený, Lukáš; Pávek, Petr; Maláková, Jana; Štaud, František; Fendrich, Zdeněk (Epilepsia, 2006)
PURPOSE: Recent studies have indicated constitutive expression of efflux transporter, breast cancer resistance protein (BCRP, ABCG2), in endothelial cells of the blood-brain barrier (BBB). In epileptogenic brain tumors such as ganglioma, astrocytoma, anaplastic astrocytomas, or glioma multiforme, strong expression of BCRP in the microvasculature of the BBB was observed. Therefore it was hypothesized that this phenomenon could critically influence the bioavailability of drugs in these tumors and potentially contribute to the failure of antiepileptic treatment. The aim of this study was to test whether some commonly used antiepileptic drugs (AEDs) are substrates transported by human BCRP. In particular, we focused on phenobarbital, phenytoin, ethosuximide, primidone, valproate, carbamazepine, clonazepam, and lamotrigine. Furthermore, the inhibitory potency of these AEDs to BCRP was examined. METHODS: To study substrate affinity of tested AEDs to BCRP, transport experiments were performed in epithelial BCRP-expressing MDCKII-BCRP and MDCKII-parent cell lines cultured on microporous membrane. For detection of inhibitory potency of AEDs to BCRP, accumulation assays were carried out in MEF3.8-BCRP cells with known BCRP substrates, BODIPY FL prazosin and mitoxantrone. RESULTS: No obvious interactions of tested AEDs with BCRP transporter were observed. Therefore these drugs in relevant therapeutic concentrations are neither substrates nor inhibitors of BCRP. CONCLUSIONS: Based on our in vitro data we can conclude that resistance to treatment with the tested AEDs probably is not caused by the overexpression of BCRP in the BBB of epileptogenic brain tumors.
Keywords: Animals; epilepsie; kapilární permeabilita; Humans; Biological Availability; Capillary Permeability; In Vitro Techniques; lidé; financování organizované; myši knockoutované; zvířata; Drug Interactions; mnohočetná léková rezistence; Drug Resistance, Multiple; myši; hematoencefalická bariéra; Financing, Organized; nádorové proteiny; transfekce; Transfection; biologická dostupnost; techniky in vitro; Cells, Cultured; antikonvulziva; lékové interakce; Neoplasm Proteins; Mice; Mice, Knockout; Anticonvulsants; endoteliální buňky; kultivované buňky; Epilepsy; Blood-Brain Barrier; Endothelial Cells